Viruses : from understanding to investigation - Payne, Susan (London : Academic Press, an imprint of Elsevier, 2017)
Viruses: From Understanding to Investigation provides students with a map for lifetime learning by presenting the definition and unique characteristics of viruses, including major topics, such as the virus lifecycle, structure, taxonomy, evolution, history, host-virus interactions and methods to study viruses. In addition, the book assesses the connections between, and among, the aforementioned topics, providing an integrated approach and in-depth understanding of how viruses work.
Includes bibliographical references and index.
Print version record.
Keywords: Viruses; SCIENCE / Life Sciences / Biology; SCIENCE / Life Sciences / Microbiology; Viruses; Viruses; Electronic books; Fulltext; Internet Resources